Study on the insulation performance of C5F10O gas mixture in cold climates - Runlong Zhang; Xiaohui Zhang; Zhilei Xu; Keliang Dong; Jinfeng Zheng; Shicheng Feng; Zhaolin Zhou; Hui Zhu (AIP Advances)
Gas-insulated switchgear (GIS) is essential for the safe, stable, and efficient operation of high-voltage power systems. Insulating gas plays a critical role in achieving electrical insulation and stable operation in GIS equipment. Perfluoropentanone (C5F10O), a novel environmentally friendly insulating gas, has gained significant attention as a potential replacement for SF6. However, C5F10O is susceptible to liquefaction in sudden drops in environmental temperature, which leads to a decrease in its insulating properties. In order to determine the parameter information that satisfies both the liquefaction temperature and insulating properties of C5F10O gas mixtures in cold climates, this paper establishes a simulation model for C5F10O gas mixtures. The model investigates the impact of temperature on the insulating properties of C5F10O gas mixtures and analyzes the physical mechanisms underlying their insulating performance in cold climates. In addition, experiments are conducted with C5F10O gas mixtures at different temperatures to observe the variation patterns of breakdown voltage at various temperatures. The insulating mechanism of C5F10O gas mixtures in cold climates is theoretically analyzed, and the characteristics of breakdown field strength with changes in buffer gas and pressure are discussed. The research findings provide theoretical data support for the application of C5F10O gas mixtures in cold climates and offer valuable references for the research and development of SF6 replacement gases.